Knowledge, prices and factor demand: Fertilizers in Argentine agriculture - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
The objective of this paper is to analyze the relative importance of knowledge inputs (or "technical change") and input prices in explaining factor demand in Argentine agriculture. Motivation for the paper is the fifteen-fold increase in fertilizer demand observed in Argentina in the 1990-2019 period. Understanding the factors affecting fertilizer use is important, as this input accounts for a significant portion of output in countries with a highly productive agricultural sector, such as the U.S. and others. In addition, increased concern for the sustainability of agricultural systems requires understanding of the economics of fertilizer use, as fertilizers can both contribute to sustainable production (via increased production not only of marketable products, but also dry matter to be incorporated to the soil), but at the same time raise issues, in particular, related to groundwater contamination and energy (in the form of fertilizer) used in the agricultural sector. Results show that in the 1990 - 2019 period increase in fertilizer demand was a result not only of a fall in the fertilizer/crop price ratio, but also on increased marginal productivity of the fertilizer input. It is suggested that this is a result of the increased importance of "knowledge inputs" in the production process.
Keywords: D24; Q10; Q12; 330; Düngemittel; Landwirtschaft; Relativer Preis; Technischer Fortschritt; Argentinien